″Implementation of the structural and functional model of the monitoring system for the development of the motor activity of future physical education teachers″ - Sokolyuk, O. V. (Problems of Engineer-Pedagogical Education, 2018)
The article describes the stages of the introduction of the structural and functional model of the system for monitoring the improvement of motor activity of future teachers of physical education, namely: I stage – creation of an information and analytical administrative laboratory; II stage – provision of managerial, educational, scientific, pedagogical support for educational activities aimed at monitoring participants of the process of professional training of future physical education teachers; III stage – raising the effectiveness of the system of monitoring the improvement of motor activity of future physical education teachers. The events (seminars, trainings, round tables, talks, topics of consultations, etc.), that contribute to the increase in the efficiency of monitoring the improvement of motor activity of future physical education teachers, are considered. It has been described that for the modernization of the educational process, the employees of the information and analytical administrative laboratory, who are teachers of the Departments of Physical Education, have developed the subject «Monitoring of Motor Activity» and included it into the curriculum. The purpose of the discipline is to help acquire professional competence regarding the use of physical education for the development of students’ recreational motor activity; organization and conducting the process of monitoring with the aim to find out the real state of recreational motor activity of different population groups.